Accumulation, activity and localization of cell cycle regulatory proteins and the chloroplast division protein FtsZ in the alga Scenedesmus quadricauda under inhibition of nuclear DNA replication - Vítová, Milada; Hendrychová, Jana; Cízková, Mária; Cepák, Vladislav; Umen, James G; Zachleder, Vilém; Bisová, Katerina (Plant & cell physiology, 2008)
Synchronized cultures of the green alga Scenedesmus quadricauda were grown in the absence (untreated cultures) or in the presence (FdUrd-treated cultures) of 5-fluorodeoxyuridine, the specific inhibitor of nuclear DNA replication. The attainment of commitment points, at which the cells become committed to nuclear DNA replication, mitosis and cellular division, and the course of committed processes themselves were determined for cell cycle characterization. FdUrd-treated cultures showed nearly unaffected growth and attainment of the commitment points, while DNA replication(s), nuclear division(s) and protoplast fission(s) were blocked. Interestingly, the FdUrd-treated cells possessed a very high mitotic histone H1 kinase activity in the absence of any nuclear division(s). Compared with the untreated cultures, the kinase activity as well as mitotic cyclin B accumulation increased continuously to high values without any oscillation. Division of chloroplasts was not blocked but occurred delayed and over a longer time span than in the untreated culture. The FtsZ protein level in the FdUrd-treated culture did not exceed the level in the untreated culture, but rather, in contrast to the untreated culture, remained elevated. FtsZ structures were both localized around pyrenoids and spread inside of the chloroplast in the form of spots and mini-rings. The abundance and localization of the FtsZ protein were comparable in untreated and FdUrd-treated cells until the end of the untreated cell cycle. However, in the inhibitor-treated culture, the signal did not decrease and was localized in intense spots surrounding the chloroplast/cell perimeter; this was in agreement with both the elevated protein level and persisting chloroplast division.
Keywords: Amino Acid Sequence; replikace DNA; DNA, Algal; bílkoviny řas; Cell Cycle Proteins; floxuridin; Floxuridine; Cyclin B; Molecular Sequence Data; proteiny buněčného cyklu; DNA řas; cyklin B; DNA Replication; Algal Proteins; buněčný cyklus; sekvence aminokyselin; molekulární sekvence - údaje; Chloroplasts; proteinkinasy; Scenedesmus; Cell Cycle; Protein Kinases; chloroplasty